Circle equation:
[tex](x-h)^2+(y-k)^2=r^2[/tex]where (h, k) is the center of the circle and r is its radius.
c) Replacing with center at (4,3) and r = 5, we get:
[tex]\begin{gathered} (x-4)^2+(y-3)^2=5^2 \\ (x-4)^2+(y-3)^2=25 \end{gathered}[/tex]d) Replacing with center at (2,-3) and r = 6, we get:
[tex]\begin{gathered} (x-2)^2+(y-(-3))^2=6^2 \\ (x-2)^2+(y+3)^2=36 \end{gathered}[/tex]a) Replacing with center at (0,0) and r = 3, we get:
[tex]\begin{gathered} (x-0)^2+(y-0)^2=3^2 \\ x^2+y^2=9 \end{gathered}[/tex]b) Replacing with center at (-2,-5) and r = 4, we get:
[tex]\begin{gathered} (x-(-2))^2+(y-(-5))^2=4^2 \\ (x+2)^2+(y+5)^2=16 \end{gathered}[/tex]